PERBUDAKAN SEKSUAL (SEXUAL SLAVERY) SEBAGAI KEJAHATAN KEMANUSIAAN DAN PERANG DI BAWAH HUKUM INTERNASIONAL - Arif Rohman (Universitas Borneo Tarakan, 2019)
Abstrac Almost every case of armed conflict both internal conflict and inter-state conflicts, violations that fall into the category of crimes against humanity. One such crime is sexual slavery. Nevertheless, the true multiple instrument products have set about sexual slavery, but in fact violations still occur, so how to regulate the instrument set up and how the application of the instrument. The approach used in this study a statutory approach and approach the case, it is intended to determine the international instruments which regulate and application of the crime of sexual slavery. Sexual slavery has been set up in several instruments and is a violation of the Fourth Geneva Conventions of 1949, Additional Protocol II of 1977, the Universal Declaration of Human Rights, the Rome Statute, anti-torture convention so that it can be regarded as war crimes. Sexual slavery is expressed as slavery not as rape. Evidently some tribunal (ICTY, ICTR, Tokyo Tribunal, and ICC) which has been in effect and entrap the perpetrators of sexual slavery was found guilty.Key words: Sexual slavery, Crime Humanity, War Crimes and International Law